A terminal germanium oxido dianion by structural constraints - Hannibal, Valentin D.; Greb, Lutz (Journal of the American Chemical Society, 2025)
Terminal oxides of late transition and main group metal(loid)s are typically highly basic and intrinsically prone to oligomerization. Their isolation traditionally relied on stabilizing π-interactions with the metal, external Lewis acids, or hydrogen bonding. Here, we present an alternative strategy: enforcing the anti-Van’t Hoff/Le Bel configuration by structural constraints. A nearly square-planar germanium center embedded in a tetra-amido macrocyclic ligand (TAML) exhibits enhanced Lewis acidity due to significant LUMO lowering. Double deprotonation of its H2O adduct affords the first example of a terminal germanium oxido dianion, [GeO]2-, which can also be seen as a first-of-its-kind monomeric, molecular germanate. Spectroscopic, crystallographic, and computational (NBO, QTAIM, and ETS-NOCV) analyses reveal a highly polarized, predominantly ionic Ge-O single bond. Reactivity studies identify this terminal oxide as a Brønsted superbase (pKa (THF) ≈ 34), a strong nucleophile, and an efficient O2- transfer agent. The findings highlight the structural constraint as an effective strategy to stabilize terminal M-O species, a structural motif of fundamental importance in bond activation, catalysis, and solid-state superbases.